(3cJGH BOGH GdCcd ef cJGH GdeMLI GdHjVGAs - (3GdcGTj Ch GdcGTGfj, , GdajV, eMeO Hf eQJVi Hf eMehO, J (B1091(3g`s ((3QeVGf Hf Ydj GdbGTGfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CMSf JOHjQ GdcGFfGJ(B... (3CeG HYO aEf ebUO Phj GdCdHGH dbGA Gddg SHMGfg hJYGdi (B... (3GdHGH GdChd ajeG dGHO ddefaQO efg hgj KdGKI CbSGe bSe bHd GdCcd (B...s
(3BNQgG (B:s
(3hCf GdedGFcI eJYHOhf HGdGSJZaGQ dTjYJg cJYHOge HGdJhMjO hGdfHhI hGdhdGjI (B...(3hdjcf gPG BNQ GdcdGe aj cJGH CNdGb GdCeGfI(B...s
(3ebGHdI aj TgQ LeGOi GdBNQ, SfI(B1098(3g`s
(3JHUQI GdeDda (B:s
(3haj GSeg NdGa(B: (3eMSf Hf eQJVi, Ch eMSf Hf eMeO, Ch eMeO eMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B617s
(3GdCYdGe(B: (3L(B5(3, U(B290s
Keywords: (3GdJUha hGdBOGH GdTQYjIs